Carbon Sequestration in Agricultural Soils - World Bank (Washington, DC, 2012)
The purpose of this report is to improve the knowledge base for facilitating investments in land management technologies that sequester soil organic carbon. While there are many studies on soil carbon sequestration, there is no single unifying volume that synthesizes knowledge on the impact of different land management practices on soil carbon sequestration rates across the world. A meta-analysis was carried out to provide soil carbon sequestration rates in Africa, Asia, and Latin America. This is one important element in decision-making for sustainable agricultural intensification, agro-ecosystems resilience, and comprehensive assessments of greenhouse mitigation potentials of Sustainable Land Management (SLM) practices. Furthermore, the ecosystem simulation modeling technique was used to predict future carbon storage in global cropland soils. Last, marginal abatement cost curves and trade-off graphs were used to assess the cost-effectiveness of the technologies in carbon sequestration. The remainder of the report is organized as follows. Chapter two provides a brief review of soil organic carbon dynamics and the methods for soil carbon assessment. The chapter concludes with brief information on carbon assessment in The World Bank's sustainable land management projects portfolio. Chapter three reports the increase in soil carbon for selected sustainable land management practices in Africa, Asia, and Latin America. Chapter four reports the estimates from ecosystem simulation, while chapter five concludes with the benefits and costs of adopting carbon sequestering practices and a discussion of policy options to support climate smart agriculture in developing countries. The report will provide a broad perspective to natural resource managers and other professionals involved in scaling up Climate-Smart Agriculture (CSA).